Risk of progression in intermediate age-related macular degeneration among patients using systemic beta-blockers - Hogan, Brady; Mehta, Nihaal; Caldwell, Anne Strong; Marin, A. Itzam; Gill, Zafar S.; Liske-Cervantes, Andres; Mathias, Marc T.; Manoharan, Niranjan; Palestine, Alan G.; Forest, Talisa E. de Carlo; Mandava, Naresh; Lynch, Anne M.; et al. (Frontiers in Ophthalmology, 2025)
PurposeThis study aims to determine whether systemic beta-blocker use over time influences the progression from intermediate to advanced age-related macular degeneration (AMD).MethodsThis prospective cohort study utilized data from the University of Colorado Age-Related Macular Degeneration Registry at the UCHealth Sue Anschutz-Rodgers Eye Center. Patients with intermediate AMD (iAMD) enrolled between October 2014 and November 2021. At enrollment, patient demographics and medication history were recorded. Beta-blocker use was assessed at enrollment and at each follow-up visit. Participants were asked to return annually for imaging, and images were classified as either intermediate AMD or conversion to advanced non-neovascular (NNV) AMD or neovascular (NV) AMD by two vitreoretinal specialists using multimodal imaging. Time to conversion was analyzed using Kaplan–Meier curves for each advanced AMD phenotype and for overall conversion, stratified by beta-blocker status. Progression from intermediate to advanced AMD (NNV or NV) was determined using multimodal imaging, including optical coherence tomography, color fundus photography, and fundus autofluorescence of the posterior pole.ResultsA total of 292 patients were included in the study, with 22.6% using a systemic beta-blocker and 36.6% (n = 107) progressing from iAMD to advanced AMD in at least one eye. Patients on a beta-blocker at enrollment were more likely to convert to NV AMD (HR: 1.92 [95% CI: 1.04, 3.55], p-value = 0.036), but this association was no longer significant after adjusting for age and treated hypertension. No significant differences were observed in conversion to advanced NNV or any advanced AMD between groups (all p > 0.05).ConclusionsIn adjusted analyses, systemic beta-blocker use was not significantly associated with the risk of progression from iAMD to advanced NV or NNV AMD.